Pedagogical innovation in the school context: from constituent elements to difficulties ans possibilities (Research, Society and Development, 2020)
This study aims to analyze the constituent elements, the difficuties and possibilities of pedagogical innovations in the school context. As a methodological procedure, bibliographic research was used in the Scielo and CCN databases, through the CAPES Portal to survey the diferente conceptions of pedagogical innovation in academic production, highlighting the aspects under analysis between May and October 2019. The results of this study point out that pedagogical innovation develops, preferably, in the classroom and in the pedagogical practices of theachers and constitutes na elementar and decisive fator for the paradigmatic changes in the education systems, something essential nowadays, in order to favor and encourage meaningful student learning. It was found that aspects such as solid teaching teams, receptive educational community, experience, reflection, evaluation, lack of intrinsic motivation of teachers for change, improvisation and lack of planning can both facilitate and hinder the processo of pedagogical innovation in the scool context.